2014
DOI: 10.1210/me.2013-1319
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted Kisspeptin Signaling in GnRH Neurons Leads to Hypogonadotrophic Hypogonadism

Abstract: Landmark studies have shown that mutations in kisspeptin and the kisspeptin receptor (Kiss1r) result in reproductive dysfunction in humans and genetically altered mouse models. However, because kisspeptin and its receptor are present in target cells of the central and peripheral reproductive axis, the precise location(s) for the pathogenic signal is unknown. The study described herein shows that the kisspeptin-Kiss1r signaling pathway in the GnRH neuron is singularly critical for both the onset of puberty as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(88 citation statements)
references
References 68 publications
5
82
0
1
Order By: Relevance
“…In human females, however, there is evidence that the same neurons in the infundibular nucleus express KISS1 [11], DYN [12], and NKB [13]. Thus, while there appear to be species and gender differences in the presence and roles of these peptides, there is a consensus that KP, signaling through its receptor (KISS1R) located on the surface of GnRH neurons, is a direct trigger of GnRH secretion in mammals [14,15,16,17,18,19,20,21,22]. GnRH then regulates the synthesis and secretion patterns of gonadotropins from pituitary gonadotropes through changes in pulse frequency and amplitude [23,24,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…In human females, however, there is evidence that the same neurons in the infundibular nucleus express KISS1 [11], DYN [12], and NKB [13]. Thus, while there appear to be species and gender differences in the presence and roles of these peptides, there is a consensus that KP, signaling through its receptor (KISS1R) located on the surface of GnRH neurons, is a direct trigger of GnRH secretion in mammals [14,15,16,17,18,19,20,21,22]. GnRH then regulates the synthesis and secretion patterns of gonadotropins from pituitary gonadotropes through changes in pulse frequency and amplitude [23,24,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Humans, mice, and rats with mutations in these genes show impaired puberty, hypogonadism, and infertility (1)(2)(3)(4)(5)(6). In addition to being expressed in reproductive areas of the brain, kisspeptin is also expressed in multiple peripheral tissues (7)(8)(9)(10).…”
mentioning
confidence: 99%
“…The selective targeting of Gpr54 deletion to GnRH neurons in this mouse line is further defined here by showing that pituitary gonadotroph responses to GnRH are intact in GnRH-Cre +/- /Gpr54 flox/flox mice. A recently published study by Novaira et al [38] using a different GnRH neuron-targeted Gpr54 -null mouse line has also shown such mice to exhibit an absence of the post-OVX increment in LH secretion. Together, these studies indicate that it is a failure of kisspeptin signaling at the GnRH neuron itself, rather than other neurons [39] or reproductive tissues [30], which is responsible for the defective negative feedback mechanism.…”
Section: Discussionmentioning
confidence: 99%